Optimasi Parameter Proses Blow Moulding Terhadap Ketebalan dan Dimensi Snap pada Botol dengan Metode Taguchi Grey Relational Analysis - Miftah Ahsanul Anhar; Fipka Bisono; Nurvita Arumsari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Blow molding is a method of printing hollow workpieces by blowing air into a molded material. From the results of the process, the specification of a product must be met by the manufacturer in fulfilling orders from the customer. The thickness of the bottle wall and the snap dimension is one of the most difficult specifications to be controlled on a 500 ml chemical bottle product. This will be resolved if the machine operator knows the optimal combination of parameters at the time of operation. In this experiment the method used is Design of Experiments with Taguchi Gray Relational Analysis method approach to get the combination between two responses taken to obtain optimal parameters. By doing a total of 27 experiments ,the experimentd were implemented on a 500 ml chemical bottle product as per specified specification. Data were collected using a digital microscope for wall thickness and dimensions vernier to snap. The result of analysis with Taguchi Gray Relational Analysis method shows that the parameters which have significant effect on wall thickness and snap bottle dimension are blowing pressure and blowing time. While the parameter of melt temperature and stop time have less significant effect. The optimal parameter setting is blowing pressure of 9 bar, melt temperature of 260 Â° C, blowing time for 7 seconds and stop time for 2 seconds.